IFRS related party transactions disclosure and firm valuation in the United Arab Emirates emerging market. Issue 2 (2nd May 2017) - Elkelish, Walaa Wahid
Abstract : Purpose: The purpose of this paper is to investigate the relationship between related party transactions disclosure ( RPTD ) and firm valuation in the United Arab Emirates (UAE), an emerging market. Design/methodology/approach: Data on study variables were obtained manually from the published financial statements of all listed companies in the stock market during the period 2008-2012. Panel regression analysis models with fixed and random effects were used to ensure reliability of results. Several robustness checks were undertaken on the study outcomes. Findings: The empirical results show that there is a significant negative relationship between RPTD and firm valuation in the UAE. RPTD s for subsidiaries and associates have the most damaging impact on firm valuation. Other control variables such as corporate governance disclosure ( CGD ), debt to equity, asset tangibility and sales growth show significant impact on firm valuation. Research limitations/implications: The potential difference in the understanding of what constitutes "related party" across companies may affect the extent of related party disclosure across companies. Furthermore, some variables are not controlled for such as ownership structure and cultural values. Practical implications: This paper provides useful practical guidelines for regulatory agencies, corporate managers and other stakeholders for improving the financial reporting system. Originality/value: RPTD was measured according to the International Financial Reporting Standards (IAS 24) standards. Furthermore, the impact of new control variables such as CGD and product market competition was tested for financial and non-financial sectors.